2021
DOI: 10.3390/ijms22020738
|View full text |Cite
|
Sign up to set email alerts
|

Polyamidoamine Dendrimers Decorated Multifunctional Polydopamine Nanoparticles for Targeted Chemo- and Photothermal Therapy of Liver Cancer Model

Abstract: The development of multifunctional drug delivery systems combining two or more nanoparticle-mediated therapies for efficient cancer treatment is highly desired. To face this challenge, a photothermally active polydopamine (PDA) nanoparticle-based platform was designed for the loading of chemotherapeutic drug and targeting of cancer cells. PDA spheres were first functionalized with polyamidoamine (PAMAM) dendrimers followed by the conjugation with polyethylene glycol (PEG) moieties and folic acid (FA) targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 55 publications
(34 reference statements)
2
13
0
Order By: Relevance
“…39 The peak above is further confirmed in the oxygen deconvolution (see Fig. 3C), where a peak is observed at ∼530.7 eV which resembles that in the studies of Chehimi et al , 40,41 where C–O − /–C–O − groups were observed and attributed to a lower conjugation of the carbonyl groups in the sample. However, it can also be attributed to the iodine content of the sample, possibly iodanil hydroquinone.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…39 The peak above is further confirmed in the oxygen deconvolution (see Fig. 3C), where a peak is observed at ∼530.7 eV which resembles that in the studies of Chehimi et al , 40,41 where C–O − /–C–O − groups were observed and attributed to a lower conjugation of the carbonyl groups in the sample. However, it can also be attributed to the iodine content of the sample, possibly iodanil hydroquinone.…”
Section: Resultssupporting
confidence: 80%
“…39 The peak above is further confirmed in the oxygen deconvolution (see Fig. 3C), where a peak is observed at ∼530.7 eV which resembles that in the studies of Chehimi et al, 40,41 where vC-O − /-C-O − groups were observed and attributed to a lower con-…”
Section: Polymer Chemistry Papersupporting
confidence: 80%
“…However, similar to all metal complexes, especially platinum drugs, they have disadvantages, the most troublesome of which is low bioavailability, which results from their high hydrophobicity [ 31 ]. Previous studies have shown that this problem can be solved by using dendrimers as drug carriers [ 32 , 33 ]. In addition, as a result of combining a drug with a dendrimer, an increase in its cytotoxicity is often observed, which allows reducing its dose and, as a result, eliminating many side effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDNPs have known place in a large number of applications including the potential treatment of periodontal disease, 22 the treatment of inflammation, 23 the potential treatment of Parkinson's disease, 24 and as an anti-cancer platform against several forms of neoplasia. [25][26][27][28] In this work, we tested the effect of PDNPs on healthy and ARSACS patient-derived fibroblasts, in terms of protective antioxidant effect and of differential protein expression. We provided the first analysis of PDNPs on an ARSACS model, and, to the best of our knowledge, this is also the first work where PDNPs have been tested on human-derived primary cells through a combination of imaging studies and proteomic analysis.…”
Section: Introductionmentioning
confidence: 99%